Transforming Inclusive Entrepreneurship Through Economic AI Literacy and Infographics: An Empowerment Program - Fakhri, M. Miftach; Andika Isma; Putri Nirmala; Nurrahmah Agusnaya; Rosidah (Yayasan Ahmar Cendekia Indonesia, 2025)
Limited access to inclusive entrepreneurial literacy, especially in areas with minimal access to education and economic resources, is a major concern. This research aims to improve teachers' competencies in using modern technologies, such as economic AI literacy, data visualization, and augmented reality, in teaching. The research method used an Action Research approach that involved three main stages, namely the preparation, implementation, and reporting stages. The results of the pre-test and post-test data showed significant improvement in the teachers' understanding and application of technology. This study concludes that the integration of economic AI and infographics is able to improve teachers' pedagogical competence in supporting inclusive entrepreneurship. However, additional time and special training are needed to optimize the application of technology in daily learning activities.